"I Have Goals to Prove All Those People Wrong and Not Fit Into Any One of Those Boxes": Paths of Resistance to Stereotypes Among Black Adolescent Males. (May 2016) - Rogers, Leoandra Onnie; Way, Niobe
Adolescents form their identities by both accommodating (endorsing) and resisting (challenging) cultural stereotypes. Most research on Black males focuses on how they accommodate to negative stereotypes (e.g., delinquency, aggression), but a growing literature emphasizes how youth resist stereotypes. Semi-structured interviews were analyzed to examine patterns of resistance and accommodation at the intersection of racial and gender stereotypes among Black adolescent males ( N = 21). Findings indicate that, overall, Black males resist racial stereotypes more readily than gender. Using an intersectionality lens, we found three paths of resistance: (a) the "accommodators" endorsed racial and gender stereotypes, (b) the "resisters" resisted both sets of stereotypes, and (c) the "exceptions" resisted racial stereotypes but accommodated to gender. Implications for the study of resistance, identity, and intersectionality are discussed.